Effect of Ration Containing Marsh Snail Meal on Protein Efficiency Ratio, Carcass And Visceral Weights of Broiler - Aisjah, T (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2004)
Marsh snail is feed commodity which has not been used as protein source in ration protein, therefore, it is important to be investigated how its effect on protein efficiency ratio, carcass and visceral weights as biological evaluation.Â This experiment used completely randomized design (CRD) consisting of 3 treatments and each of treatment was repeated 7 times and each unit experiment had 5 broilers.Â Data obtained were analyzed by variance analysis and the difference between treatments with Duncanâs test.Â Treatments of rations were R0 (fish meal 12%), R1 (unboiled marsh snail 15%), and R2 (boiled marsh snail).Â Variable observed were protein consumption, and body weight gain (to get protein efficiency ratio), carcass, liver, gizzard and kidney weights.Â The results of experiment showed that ration containing boiled marsh snail (R2) gave as good as control ration (R0) on protein efficiency ratio and gizzard weight, while carcass weight was significantly lower, and liver and kidney were significantly higher.Â Therefore, boiled marsh snail meal can be used as protein source in broiler ration with balanced amino acid. (Animal Production 6(1): 56-60 (2004)Â Key Words: Marsh Snail, Boiled, Protein Consumption, Body Weight Gain, Carcass, Visceral, Broiler